Perancangan Animasi 2D Legenda Condet Cerita Rakyat dari Jakarta Timur - Jordhy Fernando Alfon’s (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The 2D animation Legend of Condet is an artistic work that adapts a folk tale from East Jakarta, presenting the origin of Condet and the cultural values of the Betawi community. Condet has a rich historical background with local legends that contain values of courage, cooperation, environmental awareness, and cultural preservation. This animation tells the story of Astawana, a young hero who plays an important role in protecting his village from external threats. His bravery and wisdom become an inspiration for the community to maintain harmony and defend their cultural identity. This work utilizes 2D animation techniques to create attractive visual presentations through detailed illustrations, color compositions, and cultural elements that strengthen the local atmosphere. The animation incorporates Betawi characteristics, including traditional music, clothing, and everyday language, to provide an authentic representation of local culture. Beyond entertainment, Legend of Condet serves as an educational medium to introduce Indonesian folklore, history, and local wisdom to younger generations. This study employs a qualitative method through literature studies, interviews with historical experts, and direct observation of locations related to the Condet legend. The research focuses on understanding the design process of an engaging and educational 2D animation, as well as exploring the implementation of promotional strategies through launching activities and media applications. The results of this study are expected to contribute to cultural preservation efforts by utilizing animation as an effective medium for introducing local heritage in the digital era.